2-Microlocal Besov and Triebel-Lizorkin Spaces of Variable Integrability - Kempka, Henning (Revista Matemática Complutense, 2009)
We introduce 2-microlocal Besov and Triebel-Lizorkin spaces with variable integrability and give a characterization by local means. These spaces cover spaces of variable exponent, spaces of variable smoothness and weighted spaces that have been studied in recent years.